2015
DOI: 10.1159/000371551
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Isotretinoin on Ovarian Reserve Based on Hormonal Parameters, Ovarian Volume, and Antral Follicle Count in Women with Acne

Abstract: Backgroud/Aims: Widely prescribed in routine practice, isotretinoin has an unknown impact on ovarian reserve. With a long history in acne treatment and numerous potential side effects, it is surprising that very few prospective studies have investigated its effect on ovarian reserve. Therefore, we aimed to evaluate the impact of oral isotretinoin on ovarian reserve based on hormonal parameters, anti-Müllerian hormone (AMH), ovarian volume (OV), and antral follicle count (AFC) in women of reproductive age with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Sample size reference values (means, standard deviations, and reference sample sizes) were obtained from patient data observed by the authors. Taking into account all these results, our need for a total sample size is 40 for comparison [16]. The analysis was made using G ∗ Power 3.1.7.…”
Section: Power Analysismentioning
confidence: 99%
“…Sample size reference values (means, standard deviations, and reference sample sizes) were obtained from patient data observed by the authors. Taking into account all these results, our need for a total sample size is 40 for comparison [16]. The analysis was made using G ∗ Power 3.1.7.…”
Section: Power Analysismentioning
confidence: 99%
“…Isotretinoin is thought to have no side effects on male fertility, but impaired spermatogenesis findings have been reported in several animal experiments using isotretinoin administration [9]. However, several clinical studies investigating the effects of isotretinoin on female fertility have been reported to reduce ovarian reserves [10][11][12]. Similar data have been reported in animal studies in which rats were treated with 7.5 and 15 mg/kg/day isotretinoin [13,14].…”
Section: Introductionmentioning
confidence: 68%
“…In a human study, it was reported that serum AMH levels at the end of treatment of women with acne who underwent isotretinoin treatment decreased compared to serum AMH levels at the beginning of treatment, and this reduction in AMH levels has been reported to be associated with the side effect of isotretinoin on ovarian reserve [10]. In another human study, the effect of orally used isotretinoin on ovarian reserve in reproductive age women was investigated [11]. As a result of this study, when serum AMH level, ovarian volume, and antral follicles were compared before and after treatment, a significant decrease was found in posttreatment findings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies report that OIT has no impact in ovarian function. None of the studies has shown long‐term infertility (Aksoy et al, ; Öztürk et al, ). The patients were told about these two different concepts before starting OIT.…”
Section: Discussionmentioning
confidence: 99%